Marketing’s footprint in the boardroom: Antecedents and outcomes - Jones, Katheryn Jane (Curtin University, 2021)
Despite the growing influence of marketing in our everyday lives, its relevance in the executive boardroom as a valued member of the top management team continues to be debated. With this decline in the presence and contribution of marketing in the boardroom, there is a fear that organisations may ignore stakeholder perspectives jeopardising long term performance. Exploring the lived experiences of executive leaders in Australia, this research seeks to understand the obstacles faced by marketing in moving beyond middle management and playing a strategic role in organisational level decisions.